Novel hydroxy polyamine surfactant N-(2-hydroxyethyl)-N-dodecyl-ethanediamine: Its synthesis and flotation performance study to quartz - Liu, Wenbao; Liu, Wengang; Wang, Benying; Duan, Hao; Peng, Xiangyu; Chen, Xudong; Zhao, Qiang (Minerals engineering, 2019)
•NHDE was designed, synthesized and innovatively used as the collector.•NHDE displayed superior flotation performances to quartz than DDA.•Quartz/hematite separation was achieved using NHDE under pH 4.5–9.5.•Existing of multiform hydrogen bond enhanced the performance of NHDE.•The adsorption model of NHDE is proposed. A novel hydroxy polyamine surfactant N-(2-hydroxyethyl)-N-dodecyl-ethanediamine (NHDE) was designed by introducing the hydroxyethyl into diamines collector, and synthesized in the paper. The structure of NHDE was characterized by Fourier transform infrared spectroscopy (FTIR), 1H NMR and liquid chromatography mass spectrometry (LC/MS). NHDE was originally introduced as the collector in the flotation system of quartz and hematite to verify the desiliconization performance. The tests of micro-flotation, zeta potential, FTIR, and X-ray photoelectron spectroscopy (XPS) were used to study the flotation performance and adsorption mechanism of NHDE on the quartz surface. Micro-flotation results showed that NHDE exhibited outstanding performance for collecting quartz, and the efficient flotation separation of quartz from its mixture with hematite could be conducted under pH 4.5–9.5. The analysis results of zeta potential, FTIR, and XPS indicated that the adsorption of NHDE on quartz surface were due to the combination of electrostatic attractive force and the multiform hydrogen bonding. The multiform hydrogen bond not only enhanced the adsorption of NHDE on quartz surface, but also made NHDE form the stable packing layer on the quartz surface to strengthen the hydrophobic of quartz surface.